DYNAMICS OF TYPES OF CORRELATION RHYTHMOGRAMS IN EVALUATION AND PREDICTION OF ADEQUATE ADAPTATION TO THE CONDITIONS OF HIGH MOUNTAINS WITH ESTABLISHMENT OF THE OPTIMAL LIVING HEIGHT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
27 male residents of low mountains aged 20–22 years were examined, who were examined three times: in low mountains, after moving them to high mountains and in the process of readaptation. Correlation rhythmograms (CRG) were analyzed. It is noted that in the first week of stay in high altitude conditions, they have four types of correlation rhythmograms (CRG): for persons with type I (normotonic), the condition of the body with a fairly high functional reserve is characteristic; for persons with type II (sympathicotonic), there is a different degree of activity of the sympathoadrenal system; for persons with type III, the appearance of extrasystoles is characteristic; persons with type IV are characterized by a complete absence of correlation between cardiointervals. In a comparative analysis of the types of CRG in low and high mountains, three types of dynamics were established: positive – with the transition of the second type of CRG to the first type; negative – during the transition of the first type of CRG to the second, third or fourth type and neutral – the type of CRG remains unchanged. Positive dynamics indicates a favorable effect of high mountains on the body. Negative dynamics indicates either an emergency phase of adaptation, or the inability of these individuals to adapt to a given altitude, since this altitude significantly exceeds their altitude threshold.
Keywords: adaptation, highlands, altitude threshold, correlation of rhythmograms, sympathicotonya, normotoniya.